Tumor vasculature normalization by orally fed erlotinib to modulate the tumor microenvironment for enhanced cancer nanomedicine and immunotherapy. (December 2017) - Chen, Qian; Xu, Ligeng; Chen, Jiawen; Yang, Zhijuan; Liang, Chao; Yang, Yu; Liu, Zhuang
Abstract: The abnormal tumor vasculature is one of key reasons that lead to the limited tumor perfusion as well as hypoxic and immunosuppressive tumor microenvironment (TME). Herein, we uncover that by normalizing the tumor vasculature with erlotinib, a specific inhibitor of epidermal growth factor receptor (EGFR), the tumor perfusion and tumor oxygenation statuses in different types of tumors including murine breast tumors, colorectal tumors, and squamous cell carcinoma tumors, could be remarkably enhanced. As the results, the tumor uptake of drug-loaded nanoparticles as well as their interstitial penetration within the tumor would be greatly increased for mice pre-treated with erlotinib at the oral feeding dose of 50 mg/kg, leading to remarkably improved chemotherapeutic efficacy of nanomedicine. On the other hand, owing to the erlotinib-induced normalization of tumor vasculatures, the relieved hypoxic state in the three different types of tumors could alter the immunosuppressive TME into immunosupportive. Such an effect together with the increased tumor retention of anti-PDL1 antibody, a clinically approved checkpoint blockade agent, finally contributes to the greatly improved tumor inhibition effect in cancer immunotherapy. Therefore, our work presents a general yet effective strategy using a clinical drug to enhance the efficacies of cancer nanomedicine and immunotherapy by normalizing tumor vasculatures and modulating TME.